Ontology of Theistic Beliefs - Szatkowski, Mirosław (Philosophische Analyse, 2018)
This volume aims to apply ontological theories and arguments to theistic beliefs and theistic world views. After an introduction that traces out the complexity of the field by categorizing the multifaceted definitions of ontology and (theistic) believing, thirteen articles discuss specific aspects of the two terms as well as their interaction. With contributions by Chris Daly, Gabriele De Anna, Michał Głowala, Christian Kanzian, Daniel Linford, Jason Megill, Uwe Meixner, Elisa Paganini, Eleonore Stump, Mirosław Szatkowski, William F. Vallicella and Peter van Inwagen.